2022
DOI: 10.24329/aspikom.v7i1.1062
|View full text |Cite
|
Sign up to set email alerts
|

Pros and Cons of Vaccine Refusal in Social Media

Abstract: The video of rejection of COVID-19 vaccine by Ribka Tjiptaning, a public figure in Indonesia, has become one of the most popular trending news topics in various media in Indonesia. The purpose of this study is to explore the cyber community beliefs regarding COVID-19 prevention vaccination through Ribka Tjiptaning's video statement on Instagram and Facebook posts. The research was conducted on Instagram and Facebook comments with a netnographic approach by relying on the selective process theory, the concept o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The same thing happened to the implementation of the COVID-19 vaccination policy in Indonesia, which also reaped the pros and cons of cyber society. 20 This is further supported by freedom of expression and the opportunity to hide identity on social media. People in anonymity develop tendencies toward greater aggression and violence.…”
Section: Resultsmentioning
confidence: 99%
“…The same thing happened to the implementation of the COVID-19 vaccination policy in Indonesia, which also reaped the pros and cons of cyber society. 20 This is further supported by freedom of expression and the opportunity to hide identity on social media. People in anonymity develop tendencies toward greater aggression and violence.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, netnography is presented to explore and understand more about social media phenomena. Karolina & Zarkasi (2022) refer to Kozinets, mentioning nethnography is a qualitative method that seeks to understand cultural experiences reflected in social media footprints, practices, networks, and systems. This cultural experience can be involved, communicated, and reflected on, thus forming the three basic elements of netnography: investigation, interaction, and immersion.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Polemics around incidents of sexual violence on campus then also occurred in the general public, especially with the presence of digital media, which made a discourse develop quickly and expand. Various comments and discussions took place in various media, especially social media, which ultimately became a forum for conveying various opinions and could become a source of input for various government policies (Karolina & Zarkasi, 2022). It would be interesting to do further research on how the community responds to the issue regarding the Minister of Education and Culture.…”
Section: Introductionmentioning
confidence: 99%
“…In January 2023, the number of internet users reached 8.93 million (86.0%), while the number In different researches, it is reported that the uncontrolled and excessive use of social media can lead to various problems. Reseaches indicate that the unconscious and excessive use of social media applications, which are an crucial part of the internet and provide many advantages in people's lives, can have adverse impact on the business, social‖or‖personal‖areas‖of‖an‖individual's‖life‖(Griffiths‖et‖al.,‖2016),‖and‖can‖also‖lead to various psychological issues (Akram & Kumar, 2017;Dalamba, 2022).…”
Section: Introductionmentioning
confidence: 99%